Analysis Of The Influence Of Port Business Management By Pt Pelabuhan Cilegon Mandiri On The Satisfaction And Loyalty Of Vessel Service Users In Banten Port - Vicrihadi, Ariel; Kurniawan, Agus; Didik Harnoko, Eko; Maulana, Idham (Publisher Cv. Inara, 2024)
There are more than 30 port potential industrial ports which are directed to be developed and advanced, so the Banten Provincial government formed a Regional Company or Regional Owned Enterprise (BUMD), namely PD. PCM which is now PT. Cilegon Mandiri Port which has the main task of providing management and services in the field of ship guidance and towing. This research aims to determine and develop the influence of the management of Port Business Entities by PT Pelabuhan Cilegon Mandiri on the loyalty of ship service users through customer satisfaction at the Port of Banten. The research strategy used in this research is quantitative with an explanatory research approach. The research sample was 108 service users at Banten Port. The analytical tool used by SEMPLS with SmartPLS is to answer the problem formulation. The results of the research show that there is a significant positive influence of the management of Port Business Entities by PT Pelabuhan Cilegon Mandiri on the satisfaction of ship service users. There is a significant positive influence of the management of Port Business Entities by PT Pelabuhan Cilegon Mandiri on the loyalty of ship service users. There is a significant positive influence on customer satisfaction. on the loyalty of ship service users, satisfaction of ship service users is able to mediate the management of Port Business Entities by PT Pelabuhan Cilegon Mandiri on the loyalty of ship service users at Banten Port. It can be concluded that both directly and indirectly, there is an influence of the management of Port Business Entities by PT Pelabuhan Cilegon Mandiri on the loyalty of ship service users through satisfaction at the Port of Banten.